Highly sensitive bacterial susceptibility test against penicillin using parylene-matrix chip - Park, Jong-Min; Kim, Jo-Il; Song, Hyan-Woo; Noh, Joo-Yoon; Kang, Min-Jung; Pyun, Jae-Chul (ELSEVIER ADVANCED TECHNOLOGY, 2015)
This work presented a highly sensitive bacterial antibiotic susceptibility test through beta-lactamase assay using Parylene-matrix chip. beta-lactamases (EC 3.5.2.6) are an important family of enzymes that confer resistance to beta-lactam antibiotics by catalyzing the hydrolysis of these antibiotics. Here we present a highly sensitive assay to quantitate beta-lactamase-mediated hydrolysis of penicillin into penicilloic acid. Typically, MALDI-TOF mass spectrometry has been used to quantitate low molecular weight analytes and to discriminate them from noise peaks of matrix fragments that occur at low m/z ratios (m/z < 500). The beta-lactamase assay for the Escherichia coli antibiotic susceptibility test was carried out using Parylene-matrix chip and MALDI-TOF mass spectrometry. The Parylene-matrix chip was successfully used to quantitate penicillin (m/z: [PEN+H](+) =335.1 and [PEN+Na](+) =357.8) and penicilloic acid (m/z: [PA+H](+) =353.1) in a beta-lactamase assay with minimal interference of low molecular weight noise peaks. The beta-lactamase assay was carried out with an antibiotic-resistant E. coli strain and an antibiotic-susceptible E. coli strain, revealing that the minimum number of E. coli cells required to screen for antibiotic resistance was 1000 cells for the MALDI-TOF mass spectrometry/Parylene-matrix chip assay. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: FLIGHT MASS-SPECTROMETRY; ASSISTED LASER-DESORPTION; AUTODISPLAYED Z-DOMAINS; COLI OUTER-MEMBRANE; MALDI-TOF-MS; BETA-LACTAMASES; QUANTITATIVE-ANALYSIS; CARBON NANOTUBES; SMALL MOLECULES; SPR BIOSENSOR